2023
DOI: 10.1155/2023/3951752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Priming Methods on Seed Quality of Okra (Abelmoschus esculentus (L.) Moench) Genotypes

Abstract: Seed priming is an effective way of promoting seed germination and vigor of okra by alleviating seed dormancy in fresh or stored okra seeds. An experiment was carried out to evaluate the effect of seed priming treatment on seed physiological quality of okra genotypes. This experiment was conducted in a laboratory at Haramaya University in a completely randomized design with 4 replications. It comprised of 5 seed priming treatments (untreated seeds, tape water, 200 ppm GA3, 0.5% KH2PO4, and 50% cow urine) and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Based on a previous research result reported by Ref. [ 35 ], the Clemson spineless and SOH701 genotypes had a lower percentage of hard seeds than genotype 240,586 and 240,207 due to genetic differences in the laboratory conditions. As a result, seedlings from genotypes Clemson spineless and SOH701 emerged quickly from the soil, whereas those from hard-seeded genotypes 240,586 and 240,207 showed irregular and delayed seedling emergence in the field for this study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on a previous research result reported by Ref. [ 35 ], the Clemson spineless and SOH701 genotypes had a lower percentage of hard seeds than genotype 240,586 and 240,207 due to genetic differences in the laboratory conditions. As a result, seedlings from genotypes Clemson spineless and SOH701 emerged quickly from the soil, whereas those from hard-seeded genotypes 240,586 and 240,207 showed irregular and delayed seedling emergence in the field for this study.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is worth investigating suitable priming techniques for specific plant species such as okra to promote seedling emergence, establishment and productivity under different environmental conditions. Numerous studies on various seed priming methods have revealed improved seed germination and seedling vigor under controlled conditions for many crops [ 31 ], including okra [ 35 ]. However, relatively limited research has sought to evaluate the impact of different priming methods on okra across the entire growth season at field level.…”
Section: Introductionmentioning
confidence: 99%
“…Vithirak and Iwai [22] observed that vermicompost significantly increased the seed high vigor index in lettuce. GA3 may aid in seed vigor index via seed priming because this treatment is ideal for the metabolic response, enhancing seed germination efficiency, and promoting seedling growth of okra [23] . water +soil + vermicompost; T0M2 = distilled water + soil + cowdung; T0M3 = distilled water + soil + cocopeat + vermicompost; T0M4 = distilled water + soil + cocopeat + cowdung; T1M1 = GA3 + soil + vermicompost; T1M2 = GA3 + soil + cowdung; T1M3 = GA3 + soil + cocopeat + vermicompost; T1M4 = GA3 + soil + cocopeat + cowdung; T2M1 = KNO3 +soil + vermicompost; T2M2 = KNO3 + soil + cowdung; T2M3 = KNO3 + soil + cocopeat + vermicompost; T2M4 = KNO3+ soil + cocopeat + cowdung.…”
Section: Stem Diameter (Mm) and Vigor Index Of Papaya Seedlingmentioning
confidence: 99%
“…Okra (Abelmoschus esculentus L. Moench) is a popular summer vegetable crop that grows in tropical, subtropical, and temperate climates worldwide. It belongs to the family Malvaceae (Bereded Sheferie, 2023;Ziaf et al, 2022;Yadav et al, 2023a). The fibrous fruit of the okra plant provides 5.4% of its calories from carbohydrates, 4% from protein, and 0.5% from total fat, making it a highly nutritious fruit.…”
Section: Introductionmentioning
confidence: 99%
“…sagens.org/journal/agens [220] Okra growers often face the challenge of poor and inconsistent seed germination, which can lead to reduced yields and significant economic losses (Vibhuti et al, 2015;Bhandari et al, 2023). This issue is primarily caused by the hard seed coat of okra, which acts as a physiological barrier, hindering water absorption and affecting the consistency of stand establishment and overall plant health (Bereded Sheferie, 2023). Priming is a technique used in okra farming to enhance seed germination (Wahocho et al, 2023).…”
Section: Introductionmentioning
confidence: 99%